Point-count analyses of grains from the Nankai subduction zone (Japan) at IODP Site 348-C0002 - Pauline Cornard; Harriet Dawson; Kevin T Pickering (PANGAEA, 2024)
For petrographic analyses, point counting was used to quantitatively estimate the modal composition of sand and sandstones by totalling the occurrence of various mineral grains within a representative sample. The Gazzi-Dickinson methos was chosen for this study. A total of 80 cutting and core samples from IODP Expedition 348 were used for this study, covering a total depth transect from 1,140.5-3,000.5 mbsf of the Nankai Accretionary Prism (SW Japan) at sites C0002N and C0002P. All 80 samples were prepared for thin sections for quantitative modal compositional analysis at The Open University (United Kingdom). Samples were sieved to remove clay and silt from the unconsolidated material. Approximately 10 grams of sands were then separated from the sieved samples and mixed with epoxy. The epoxy grain mounts were sliced to thin section thickness, cemented to glass slides with epoxy resin, and then thin sections were completed in the usual method. Point-count analyses involved 400 points per sample. Each grain was assigned to a classification category (e.g., monocrystalline quartz, polycrystalline quartz, feldspar, volcanic lithic, sedimentary lithics, etc).